Plasma levels of soluble VEGF receptor isoforms, circulating pterins and VEGF system SNPs as prognostic biomarkers in patients with acute coronary syndromes - Marks ECA; Wilkinson TM; Frampton CM; Skelton L; Pilbrow AP; Yandle TG; Pemberton CJ; Doughty RN; Whalley GA; Ellis CJ; Troughton RW; Owen MC; et al. (BioMed Central Ltd)
BACKGROUND: Development of collateral circulation in coronary artery disease is cardio-protective. A key process in forming new blood vessels is attraction to occluded arteries of monocytes with their subsequent activation as macrophages. In patients from a prospectively recruited post-acute coronary syndromes cohort we investigated the prognostic performance of three products of activated macrophages, soluble vascular endothelial growth factor (VEGF) receptors (sFlt-1 and sKDR) and pterins, alongside genetic variants in VEGF receptor genes, VEGFR-1 and VEGFR-2. METHODS: Baseline levels of sFlt-1 (VEGFR1), sKDR (VEGFR2) and pterins were measured in plasma samples from subgroups (n = 513; 211; 144, respectively) of the Coronary Disease Cohort Study (CDCS, n = 2067). DNA samples from the cohort were genotyped for polymorphisms from the VEGFR-1 gene SNPs (rs748252 n = 2027, rs9513070 n = 2048) and VEGFR-2 gene SNPs (rs2071559 n = 2050, rs2305948 n = 2066, rs1870377 n = 2042). RESULTS: At baseline, levels of sFlt-1 were significantly correlated with age, alcohol consumption, NTproBNP, BNP and other covariates relevant to cardiovascular pathophysiology. Total neopterin levels were associated with alcohol consumption at baseline. 7,8 dihydroneopterin was associated with BMI. The A allele of VEGFR-2 variant rs1870377 was associated with higher plasma sFlt-1 and lower levels of sKDR at baseline. Baseline plasma sFlt-1 was univariately associated with all cause mortality with (p < 0.001) and in a Cox's proportional hazards regression model sFlt-1 and pterins were both associated with mortality independent of established predictors (p < 0.027). CONCLUSIONS: sFlt-1 and pterins may have potential as prognostic biomarkers in acute coronary syndromes patients. Genetic markers from VEGF system genes warrant further investigation as markers of levels of VEGF system components in these patients. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry. ACTRN12605000431628 . 16 September 2005, Retrospectively registered.
Keywords: sFlt-1; KDR; Neopterin; Acute coronary syndromes; Mortality; Prognosis; 1102 Cardiorespiratory Medicine and Haematology